Applying ‘cultural humility’ to occupational therapy practice: a scoping review protocol - Hardeep Singh; Michelle L A Nelson; Heather Colquhoun; Kristina Marie Kokorelias; Tram Nguyen; Ruheena Sangrar; Sachindri Wijekoon; Erica Nekolaichuk; Sofia Mirzazada; Holly Assaf (BMJ Open)
Introduction Cultural humility is becoming increasingly important in healthcare delivery. Recognition of power imbalances between clients and healthcare providers is critical to enhancing cross-cultural interactions in healthcare delivery. While cultural humility has been broadly examined in healthcare, knowledge gaps exist regarding its application in occupational therapy (OT) practice. This scoping review protocol aims to: (1) describe the extent and nature of the published health literature on cultural humility, including concepts, descriptions and definitions and practice recommendations, (2) map the findings from objective one to OT practice using the Canadian Practice Process Framework (CPPF), and (3) conduct a consultation exercise to confirm the CPPF mapping and generate recommendations for the practice of cultural humility in OT.Methods and analysis We will search Ovid Medline, Ovid Embase, Ovid PsycINFO, Ebsco CINAHL Plus, ProQuest ASSIA, ProQuest Sociological Abstracts, ProQuest ERIC, WHO Global Index Medicus, and Web of Science databases. Published health-related literature on cultural humility will be included. There will be no restrictions on population or article type. Following deduplication on Endnote, the search results will undergo title, abstract, and full-text review by two reviewers working independently on Covidence. Extracted data will include descriptors of the article, context, population, and cultural humility. After descriptive extraction, data describing cultural humility-related content will be descriptively and interpretively analysed using an inductive thematic synthesis approach. The data will also be mapped to OT practice through deductive coding using the CPPF. Occupational therapists and clients will be consulted to further critique, interpret and validate the mapping and generate practice recommendations.Ethics and dissemination Ethics approval was not required for this scoping review protocol. We will disseminate the findings, which can enhance understanding of cultural humility in OT, facilitate cross-cultural encounters between occupational therapists and clients and improve care outcomes through publications and presentations.